Variabilité Climatique Et Savoirs Endogènes En Pays Torri Dans La Commune De Akpro-Misserete - VISSIN Expédit Wilfrid (European Scientific Journal, ESJ, 2016)
Climate variability as well as extreme phenomena have various interpretations. These last depend on agricultural practices and endogenous ritual related to a specific ethnic group. The study aims at analyzing endogenous perceptions about hydroclimate phenomena of Torri populations of the district of Akpro-Missérété in Benin. The adopted methodology is based on the collection and process of climatic and hydrological data. The climatic data were rainfall and temperature. All the data cover the period from 1971 to 2010. These scientific data were compared with endogenous knowledge related to hydroclimate phenomena in the study area. The results showed that Torri populations of the district of Akpro-Missérété have endogenous knowledge allowing them to recognize and to predict the succession of the climatic phenomena. Thus, the long wet season is indicated by ‘’Amajikun’’; the short one covering September and October is called ‘’Ozojikùn’’. The long dry season is called ‘’Akudaxo’’ whereas the short one is known as '’Akukpɛvi''. The drought period is recognized by the persistence of rainfall recession and called ‘’Akugaa’’, whereas the period of high waters is known as ''Tɔgigɔ''. These various climatic phenomena constitute the agricultural schedule which is similar to agricultural season. In case of extreme phenomena, Torri populations develop adaptation strategies. These included early crop harvest or postponed harvest depending on the rainfall rate. Also, they organized ceremonies and offerings to the gods to ward off evil spells in order to regulate agricultural activities.